Putting the serial in context: Comparing the storytelling processes of contemporary primetime Kuwaiti television dramas with American network dramas - Ahmad Hayat (Series. International journal of tv serial narratives, 2020)
Strictly designed with distinct narrative characteristics to accommodate the thirty day schedule of the holy month of Ramadan, Kuwaiti television dramas broadcast in a proliferated television landscape confined by the Arabic language and consists of television institutions operating from various Arab countries that compete for the vast pan-Arab audience. These unique broadcasting conditions inform the programme-making practices that shape the construction of narratives across the pan-Arab region. Like American network dramas, Kuwaiti dramas depend on advertising and syndication to generate revenue but the pan-Arab region’s technological adaptation transformed the production conditions and the commissioning processes of these dramas. By comparing the commissioning process of Kuwaiti television dramas with American network dramas, this article examines the development of the storytelling practices involved in shaping their narrative conventions and illuminates the manifestation of their industrial specificities in their narrative designs. The analyses of primary interviews with writers and representative dramas suggest that the unique shared broadcasting conditions of the pan-Arab region, accompanied by the particular operations of a television industry within the region, contribute to the commissioning process and designs of television dramas, and the challenges of this competitive language-confined environment underpins the prominent and intense implementation of serialized elements in Kuwaiti television dramas.